COMPARISON OF POST PLACENTAL INTRAUTERINE CONTRACEPTIVE DEVICE INSERTION BETWEEN VAGINAL DELIVERY AND CAESAREAN SECTION IN A TERTIARY CARE HOSPITAL - Tasneem, Saira; Kashif, Sanum; Pervaiz, Erum; Azam, Faisal (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the acceptability of insertion of post placental intra uterine contraceptive device, withrespect to gravidity between vaginal deliveries and caesarean sections.Study Design: Prospective comparative study.Place and Duration of Study: Frontier Corp Hospital, Quetta, from Jan 2019 to Jan 2020.Methodology: A total of 399 females with age of 18 to 45 years with gravidity (primi, multi and grand multigravida) were counselled during antenatal visits about benefits and risks of post placental intrauterine contraceptive device (PPIUCD) insertion. For complications, females were assessed at 1 and 6 weeks after delivery.Results: A total of 399 females with mean age 27.95 ± 5.07 years were included in study. About 235 (55.9%)women delivered vaginally and 164 (41.4%) women by caesarean section. Acceptance rate was 3.8% and 4.3% for vaginal and caesarean deliveries respectively. Eleven (73.3%) women were grand multi gravida and 4 women(26.6%) were multi gravid in vaginal delivery acceptance group versus 8 women (47%) grand multi and 9 women (52.9%) multi gravida in caesarean acceptance group. Five (15%) females presented with complications (3 with abdominal pain and 1 each with infection and expulsion).Conclusion: The overall acceptance rate of PPIUCD was low in this study, the acceptance rate was higher inwomen undergoing normal vaginal delivery (NVD) as compared to lower segment caesarean section (LSCS),similarly more of the grand multiparas accepted the method as compared to other participants however thedifferences were not statistically significant.